Imagining the postcolonial : discipline, poetics, practice in Latin American and Francophone discourse - Hanneken, Jaime, 1978- (State University of New York Press, 2015)
A comparative study of Latin American and francophone postcoloniality. Imagining the Postcolonial is the first book dedicated to comparative analysis of Latin American and francophone postcolonial identity. Jaime Hanneken examines the disciplinary, theoretical, and political stakes involved in postcolonial identification in non-anglophone cultural spheres through readings of José Lezama Lima and Édouard Glissant's poetics of place, the symbolic value of Paris in modernista writing and in Congolese Sociétés des Ambianceurs et Personnes Élégantes (sape) rituals, and the scandals surrounding Rigoberta Menchú and Yambo Ouologuem. Hanneken argues that reorienting comparative critique to the priority of the object of study can transform rather than replicate existing conceptual formats of postcoloniality.